MODERN WEDDING IN THE MOUNTAIN VILLAGE OF KUBACHI (BASED ON THE FIELD MATERIAL OF 2017-2018): KEY RITES, LOCAL FEATURES - Gadzalova, Fatima Amirbekovna (History, Archeology and Ethnography of the Caucasus, 2022)
The paper is based on the field ethnographic material, collected in the village of Kubachi, Dakhadaevsky district of Dagestan. The methods of participant observation, survey and interview with the villagers of Kubachi and the urban Kubachins have been applied for collecting the material for the study. The Kubachi wedding is a complex of specific customs and rituals, which last for three days in a certain sequence within the context of the mountain village. Local features and key points of a modern rural wedding are described. The author considers the traditional festive women’s costume as part of the whole wedding ceremony: these are dresses of a bride and closest married women of the family. Features of a collective wedding procession, which carries a certain function for each of the three days of the ceremony, are discussed: repeating the rite of matchmaking with gifts on the first day, the relocation of the bride with relatives to the groom’s house on the second day, and the transfer of dowry on the third day of the wedding. The custom of the wedding ritual-show in the open air, accompanied with food and music, dances and mummers’ games is revealed. The material on the types of wedding food, traditions of its cooking is considered. The paper also discusses the custom of good-wishing and magic rituals, performed during the wedding, as well as the symbolism and their function. Among these rituals are: showering the bride with sweets, concealing the face with a veil, honey treating; features of popular magic beliefs on even numbers are also mentioned. The study also proposes material on city weddings of the Kubachins, their traditional rites, performed in an urban setting: women’s festive dress, traditional dances, etc.